Pinkgola - restaurant finder mobile apps - Tiew, Kai Wen (2019)

(untitled)
This application aims to solve the problem of indecisive minded people to make their decision for their daily meal. Based on past studies, people are found hard to make a decision given with various alternative options (Dhar 1997.). Making decisions on daily meals mean significant effort for them. There is various type of restaurants in the market and all of these restaurants having a list of food items. Restaurants are one of the parties that contribute the most on generating options for indecisive people. Reviewing all option and make a decision will be a time-consuming act for them. All their needs is a restaurant finder mobile application that provides suggestion on food item based on their user preference. Even though existing restaurant finder app can provide indecisive minded people with food information, the apps still do not solve the problem of the indecisive minded people. This is because the existing application generates more option for their user to choose from, it is not convenient for them as it needs extra effort to make a decision. The proposed application will be developed to provide a solution to solve the problem of indecisive minded people. The proposed application will provide a suggestion of food item by sorting out options with series of a customized filter. Firebase Firestore and Google Maps Service are used in this project. Agile methodology will be used to fit this mobile application development lifecycle.